GE_GERICHTE P/21767/2015 vom 2. März 2021 - GE Cour de justice (2021)
PLAINTE PÉNALE;DÉLAI;CLASSEMENT DE LA PROCÉDURE;LÉSION CORPORELLE GRAVE;LÉSION CORPORELLE SIMPLE;MISE EN ACCUSATION | CP.31; CP.125; CP.122; CPP.9; CPP.319; CPP.429